1921 Wyo. Sess. Laws 112-13, ch. 83, § 97. - (:unkn) unknown (My University, 1921)
It shall be unlawful for any person to take into the game fields or forests of this State, or have in possession while in the game fields or forests of this State, or to have in possession while out for the purpose of hunting the game animals or game birds of this State any device or mechanism designed to silence or muffle or minimize the report of any firearm, whether such device or mechanism be separated or attached to any firearm or not.
Keywords: HUNTING REGULATION; SUPPRESSORS